An Innovative Tray Device to Measure Taper and Relative Parallelism of Abutment Teeth for Fixed Dental Prosthesis - Shefali Singla, Lalit Kumar, Charnpreet Singh, Shrishti Bhardwaj, Komalpreet Kaur (RUHS Journal of Health Sciences)
Various methods available to determine parallelism of abutment teeth are either unreliable, require costly instruments, or involve additional complex steps. This communication describes an intraoral device to determine parallelism of prepared abutments chairside which is a U-shaped stock tray that helps to determine parallelism by placing paralleling pins in the moving troughs along the multiple abutment teeth. Angle of paralleling strip can be measured using sliding protractor. It is a tool that aids clinicians in visualizing tooth abutments for parallelism, identifying undercuts, and reducing over-tapering before definitive impression without requirement of any additional step or expensive equipment.